2020
DOI: 10.3390/cells9122650
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Group Box-1 and Blood–Brain Barrier Disruption

Abstract: Increasing evidence suggests that inflammatory responses are involved in the progression of brain injuries induced by a diverse range of insults, including ischemia, hemorrhage, trauma, epilepsy, and degenerative diseases. During the processes of inflammation, disruption of the blood–brain barrier (BBB) may play a critical role in the enhancement of inflammatory responses and may initiate brain damage because the BBB constitutes an interface between the brain parenchyma and the bloodstream containing blood cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 176 publications
(261 reference statements)
1
48
0
Order By: Relevance
“…Our meta-analysis found that METH increased expression of HMGB1, which, in turn, leads to disruption of the blood brain barrier (BBB), neuronal damage, formation of amyloid-beta plaques, and an overall increase in APP expression ( Figure 10 ). These data were in line with prior findings on the relationship between HMGB1 and its effects on the BBB and APP [ 10 , 11 , 12 , 13 , 32 , 33 ] to demonstrate METH modulation on APP, the precursor of beta amyloid, through HMGB1 in AD development.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our meta-analysis found that METH increased expression of HMGB1, which, in turn, leads to disruption of the blood brain barrier (BBB), neuronal damage, formation of amyloid-beta plaques, and an overall increase in APP expression ( Figure 10 ). These data were in line with prior findings on the relationship between HMGB1 and its effects on the BBB and APP [ 10 , 11 , 12 , 13 , 32 , 33 ] to demonstrate METH modulation on APP, the precursor of beta amyloid, through HMGB1 in AD development.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, HMGB1 is seen on the Aβ plaques in AD brains [ 10 ] and enhances the neurotoxicity of Aβ [ 11 ]. HMGB1 has also been found to mediate disruption of the blood-brain barrier (BBB) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High mobility group box-1 (HMGB1), a highly conserved nonhistone nuclear protein, plays a particularly important role as proinflammatory factor in the extracellular space through the stimulation of plural receptors: receptor for advanced glycation end products, toll-like receptor-4/2 (35). HMGB1 is released from not only necrotic cells but also many kinds of living cells under different conditions of stress including hypoxia, ischemia, and stimulation by cytokines (36,37). The neutralization of extracellular HMGB1 by specific monoclonal antibody (mAb) was reported to inhibit influenza virus (H1N1)-induced pneumonia and improve the survival of infected mice (38,39).…”
Section: High Mobility Group Box-1 As An Important Dampmentioning
confidence: 99%
“…High mobility group box 1(HMGB1) not only plays a critical role as a nuclear DNA-binding protein, but also as a cytokine-like mediator of systemic in ammation, for example, HMGB1 plays an important role in BBB damage after stroke (Nishibori et al 2020). In addition, serum HMGB1 levels were signi cantly elevated in patients with cerebral ischemia (Goldstein et al 2006) and HMGB1 has been reported to be released from neurons early following ischemic injury, and acts as a mediator linking acute brain damage and subsequent in ammatory processes (Qiu et al 2008).…”
Section: Introductionmentioning
confidence: 99%